Association of Asthma and Allergic Rhinitis With Sleep-Disordered Breathing in Childhood - Perikleous, Evanthia; Steiropoulos, Paschalis; Nena, Evangelia; Iordanidou, Maria; Tzouvelekis, Argyrios; Chatzimichael, Athanasios; Paraskakis, Emmanouil (Frontiers in Pediatrics, 2018)
Objective: Asthma and allergic rhinitis (AR) are the most common chronic conditions in childhood and have previously been linked to sleep-related breathing disorder (SRBD). Aim of the study was to examine the association between SRBD risk and asthma control in children with asthma and with or without AR. Methods: The assessment of FeNO and pulmonary function tests were performed in 140 children (65 with asthma, 57 with both asthma and AR, 18 with only AR). Children with asthma completed the childhood Asthma Control Test (c-ACT), and the Sleep-Related Breathing Disorder scale, extracted from the Pediatric Sleep Questionnaire (PSQ). C-ACT scores ≤ 19 are indicative of poor asthma control whereas SRBD from PSQ scores ≥ 0.33 are suggestive of high risk for SRBD. Results: Mean age±SD was 7.8±3.1 years. Mean PSQ±SD and c-ACT±SD scores were 0.17±0.14 and 24.9±3.2, respectively. High risk for SRBD was identified in 26 children. Children at high risk for SRBD had significantly decreased c-ACT score (P=0.048), verified by a negative association between c-ACT and PSQ-SRBD scores (r=-0.356, P<0.001). Additionally a difference in diagnosis distribution between children at high or low risk for SRBD was observed. More specifically, among children at high risk, 88.5% were diagnosed with both atopic conditions, while this percentage among children at low risk was 29.8%. Asthma was mainly diagnosed in the latter group (P<0.001). Conclusions: Poor asthma control is associated with SRBD. The presence of AR in children with asthma seems to increase the prevalence of SRBD in that particular population, requiring further investigation towards this direction.